LANGUAGE USE AND LANGUAGE ATTITUDES OF BILINGUAL TURKS IN BULGARIA - Yusufoff, Yasemin (European Scientific Journal, ESJ, 2014)
In this paper is summarized a study of language practices and language attitudes of bilingual ethnic Turks in Bulgaria. As assumed, speaking Bulgarian in small Turkish village settings is not common, and speaking Turkish in urban, and otherwise predominantly Bulgarian settings is frowned upon. Since the fall of the Ottoman Empire, Bulgaria’s language policies aimed to restrict Turkish language and this study confirms that these longterm policies are successful.